Achaete-Scute Homolog 1 Expression Controls Cellular Differentiation of Neuroblastoma - Kasim, Mumtaz; Heß, Vicky; Scholz, Holger; Persson, Pontus B.; Fähling, Michael (Frontiers in Molecular Neuroscience, 2016)
Neuroblastoma, the major cause of infant cancer deaths, results from fast proliferation of undifferentiated neuroblasts. Treatment of high-risk neuroblastoma includes differentiation with retinoic acid (RA); however, the resistance of many of these tumors to RA-induced differentiation poses a considerable challenge. Human achaete-scute homolog 1 (hASH1) is a proneural basic helix-loop-helix transcription factor essential for neurogenesis and is often upregulated in neuroblastoma. Here, we identified a novel function for hASH1 in regulating the differentiation phenotype of neuroblastoma cells. Global analysis of 986 human neuroblastoma datasets revealed a negative correlation between hASH1 and neuron differentiation that was independent of the N-myc (MYCN) oncogene. Using RA to induce neuron differentiation in two neuroblastoma cell lines displaying high and low levels of hASH1 expression, we confirmed the link between hASH1 expression and the differentiation defective phenotype, which was reversed by silencing hASH1 or by hypoxic preconditioning. We further show that hASH1 suppresses neuronal differentiation by inhibiting transcription at the RA receptor element. Collectively, our data indicate hASH1 to be key for understanding neuroblastoma resistance to differentiation therapy and pave the way for hASH1-targeted therapies for augmenting the response of neuroblastoma to differentiation therapy.